Dedicatory Latin Inscriptions on the Church of St. John of Biranj (Archaeologia Adriatica, 2010)
Within the archaeological-historical complex at the hillfort of Biranj (Kaštel Lukšić), the ancient church of St. John the Baptist stands out in particular as a cultural entity. Three architectural phases (Romanesque, Late Gothic, and Modern period) can be perceived in its present appearance. The façade of the church bears a group of late medieval inscriptions in Latin: a donative inscription on the lintel, dated 1444 and also by the reign of the Venetian Doge Francesco Foscari (today placed in the interior of the church), as well as four consecratory inscriptions from the same time on the corners of the church. They were placed by donors (church juspatronatus) on the structure of the church on the occasion of the dedication of the thoroughly renovated original church of St. John, which had been built in the Romanesque period, at the end of the 12th or in the early 13th century, as the endowment of the Ostrog free villagers. From the donative inscription on the lintel it is learned that the ruinous Romanesque church was renovated from the foundations up by the juspatronus and plebanus Grgur Nikolin, the archpresbyter and canon of the Trogir diocese, in the name of a personal vow and the vows of all the juspatroni of St. John of Biranj. The four consecratory inscriptions with the text + Christus venit in pace et Deus homo factus est on the corners of the Late Gothic church from the same period are particularly interesting. On the basis of the contents it is hypothesized that they represent some kind of reminiscence of the possible original epigraphic dedications from the period of the construction of the Romanesque church at the end of the 12th century or in the early decades of the 13th century. The inscriptions and the sacred structure to which they belong are considered in the framework of the site as a cultural-historical complex and multi-century religious shrine and are analyzed in terms of the formal and contextual epigraphic traits. Their context is explored in the framework of the historical and religious-spiritual conditions related to the specific area in the period of the developed (12th and 13th centuries) and late Middle Ages (middle of the 15th century).
Keywords: Biranj; St. John the Baptist; consecratory inscriptions; Incarnation